Konsep Al-Shifā’ dalam Al-Qur’an: Kajian terhadap metode rawatan Ibn Qayyim Al-jawziyyah / Zulkiflee Haron - Zulkiflee, Haron (2016)

(untitled)
This study employed an analytical analysis on the methods of therapy of Ibn Qayyim based on his writings. It was aimed at understanding and analyzing the thinking of Ibn Qayyim in his medical therapy which comprises the physical and spiritual aspects as well as the influence of the surroundings of his on his style of writing. On the other hand, the specific objective is to uncover Ibn Qayyim’s views toward the six ayat alshifā’ (verses of healing) in the holy Quran and his concept of al-shifā’ (healing) derived from the Quran and al-Hadith. The study also scrutinized his principles and methods of therapy and medicinal school of thought. As a result, the reseacher was able to formulate a model of Ibn Qayyim’s therapy methods as well as indentify the elements to be evaded while practising the method. The method of study was thematic and hermeneutics analysis as well as philosophical interpretation. It was found that Ibn Qayyim being a respected Muslim scholar was able to boldly promote an Islamization to the medical discipline which is more holistic in nature. In order to balance the scholarship thinking culture and societal needs, he uses the approach which was spiritually value laden and emphasizes ishtibak (traversity) in the medical practice. This is so to establish revealed sources as the primary reference with the human sources as secondary references in the al-shifā’ method of therapy. Through his method of therapy, Ibn Qayyim was able to show his inclination towards the development of spiritual potentials and inner faculties of a human being in achieving healing.